2000
DOI: 10.1046/j.1523-1755.2000.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone receptor abundance in tibial growth plates of uremic rats: GH/IGF-I treatment

Abstract: These studies point to a mechanism for the growth retardation seen in children with CRF, and suggest that combined GH/IGF-I treatment may provide more effective therapy for these patients than GH alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
4
23
1
2
Order By: Relevance
“…However, an increased growth plate cartilage height has not been consistently found in uremic rats. Uremic growth plate size greater than [1,6,9,11,12,14], similar to [2,4,5,8,10,11,13,14] or even smaller than [7,8] that of control animals has been reported. The reasons for this disparity are unknown.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, an increased growth plate cartilage height has not been consistently found in uremic rats. Uremic growth plate size greater than [1,6,9,11,12,14], similar to [2,4,5,8,10,11,13,14] or even smaller than [7,8] that of control animals has been reported. The reasons for this disparity are unknown.…”
Section: Introductionmentioning
confidence: 72%
“…Several studies have analyzed the tibial growth plate of young uremic rats in an attempt to clarify the mechanisms underlying growth impairment in chronic renal failure [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. There is interest in studying the growth plate in this animal model because this is where longitudinal growth takes place and it cannot be studied in children.…”
Section: Introductionmentioning
confidence: 99%
“…Growth responses of uremic chondrocytes were reduced to GH and IGF-I specifically, since growth responses to fibroblast growth factor and transforming growth factor were normal [57]. A study of uremic rats showed a reduction in GHR density in tibial growth plate [58] and low levels of mRNA for hepatic GH receptor [59]. In addition, there is evidence from animal studies that IGF-I resistance also arises from tissue insensitivity caused by a post-receptor defect in IGF-I-mediated signal transduction [60], although the site of the abnormality is controversial [61].…”
Section: Gh-igf-i Insensitivity and Growth Failure In Ckdmentioning
confidence: 99%
“…Some reports have described reduced hepatic GHR mRNA and growth plate GHR protein levels in rats with CRF [28,29]. Other animal studies have suggested that the receptor protein levels are unaltered by uremia per se [25,26,27], but that reduced food intake is the cause of the GHR changes [25,30].…”
Section: Alterations In Gh Receptor Expressionmentioning
confidence: 99%